(untitled) (Italian Journal of Public Health, 2008)
Epidemiology can be considered a cornerstone of the Health Sciences, since it aims at studying factors affecting the health and illness of particular populations. The work done by the Epidemiologists can be useful as the foundation of health interventions realised in the fields of public health and preventive medicine.